Manipulation of language: an ancient power and an ever-innovative weapon - Huanca Quispe, Jaime (2003)
The theme we have chosen makes it inevitable to focus with special attention on a serious problem that has plagued the country for several centuries. It is an issue that has always been postponed and ignored, because it denotes the political abuse of all governments. It is especially avoided every time that "the finger is put in the wound", when finally it is a question of reaching a fair and humane dialogue with the government and its relevant authorities.